Структура генотипової мінливості кількісних ознак гібридів F₁ сої - Білявська, Л.Г.; Корнєєва, М.О. (Фактори експериментальної еволюції організмів, 2013)
Aims. To investigate the structure of genotypic variation of agronomic characters in topcross soybean hybrids. Methods. On the basis of dispersion analysis of topcross hybrids the parts of additive and non-additive gene effects of parental components have been determined. Results. Characters with mostly additive (plant height, number of nodes on the main stem) and non- additive (number of pods per plant, number of branches per plant and the lower pod height) gene effects have been determined. That allows choosing the strategy of their breeding and genetic improvement. Some heterosis hybrids were selected in order to search for transgressive soybean forms. Conclusions. It has been determined that additive gene effects mostly influenced genetic control of such traits as number of nodes on the main stem and plant height, while non-additive effects of gene interaction were more significant in genetic control of the number of pods per plant, number of branches per plant and the lower pod height.

Key words: soybeans, topcross hybrids, gene interaction, heterosis.